Seroprevalence of syphilis and associated factors among pregnant women who attended antenatal care follow-up at public hospitals in Bahir Dar city, north-west Ethiopia: a cross-sectional study - Bantayehu Nega Arega; Wassihun Ayeligne Wassie; Lakachew Asrade Feleke; Adela Menberu Alemu (BMJ Public Health)
Background Syphilis, caused by Treponema pallidum, remains a significant global public health concern, especially among pregnant women due to its severe impact on maternal and fetal health. Although the burden of syphilis and its risk factors has been extensively studied worldwide, data specific to Bahir Dar, particularly within the context of three public hospitals, remain limited. This is further compounded by the inconsistent implementation of existing prevention and treatment policies. Untreated syphilis can lead to adverse pregnancy outcomes, including spontaneous abortion, stillbirth, early neonatal death and congenital syphilis. This study aimed to assess the seroprevalence of syphilis and associated factors among pregnant women attending antenatal care (ANC) at three public hospitals in Bahir Dar, North-West Ethiopia.Methods A cross-sectional study was conducted among 551 pregnant women attending ANC at Tibebe Ghion Specialized Hospital, Felege Hiwot Comprehensive Specialized Hospital and Addis Alem Hospital from January to April 2023 Gregorian Calender (G.C). Participants were selected using systematic random sampling, and data were collected through structured interviews using a pretested questionnaire. Data were processed using EpiData V.3.1 and analysed with SPSS V.25, employing bivariate and multivariable logistic regression to identify significant factors.Results The seroprevalence of syphilis was 2.4% (95% CI: 1.3-3.8), with a higher prevalence among urban residents (3.6%) compared with rural residents (1%). Significant associations were found between syphilis prevalence and a history of stillbirth (adjusted OR (AOR)=7.28; 95% CI: 1.05-24.87) and a history of active or previous sexually transmitted infections (AOR=5.3; 95% CI: 1.23-22.52).Conclusion The study’s seroprevalence aligns with previous findings, emphasising the need for routine syphilis screening and treatment in ANC services. Special attention should be given to women with a history of stillbirth, other adverse pregnancy outcomes or sexually transmitted infections. Enhanced counselling on syphilis screening and treatment is essential to reduce the burden of syphilis and improve maternal and fetal health outcomes.